A Study on Teaching Speaking at English Education Department of Universitas Islam Madura - Rini Listyowati; Ina Daril Hanna (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study was purposed to describe the difficulties in linguistics faced by the students in studying Speaking and the ways taken by the lecturer in solving the students’ linguistics difficulties in studying Speaking at English Education Department of Universitas Islam Madura.The research design was descriptive and the subject of the study was fourth semester students and Speaking Lecturer of English Education Department. The data were collected by observing the Speaking lecturer and interviewing the six students and speaking lecturer. They were analyzed descriptively. The finding showed that the materials used in teaching speaking are Describing Object, Simple present and Vocabulary. Meanwhile, the strategies which are used by the lecturer are lecturing, individual task, group discussion, students’ performance and role play. The Speaking lecturer had some ways to solve the linguistic difficulties by making the class attractive, giving more detailed explanation and some exercises, giving more detailed explanation in the usage of tenses and some exercises, giving the vocabulary , and identifying the difficulties dealing with the students’ condition.